2006
DOI: 10.1111/j.1075-122x.2006.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic and Aesthetic Results Following Breast-Conserving Therapy with 0.5 cm Margins in 100 Consecutive Patients

Abstract: The purpose of this study was to evaluate the oncologic and aesthetic results of patients undergoing breast-conserving therapy with 0.5 cm surgical margins and determine the factors that influence the need for reconstruction. One hundred consecutive patients who underwent breast-conserving surgery with 0.5 cm surgical margins followed by radiotherapy for invasive cancer and ductal carcinoma in situ (DCIS) were followed prospectively and evaluated for recurrence and aesthetic result. Thirteen patients underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 21 publications
(19 reference statements)
1
26
0
Order By: Relevance
“…26,41,44 Although great strides have been made in breast conserving therapy, the invasive nature of surgical resection oftentimes results in significant scarring and disfigurement, with approximately 20% of patients undergoing breast-conserving therapy unsatisfied with their final breast cosmetic outcome. 13,16 Such cases may undergo additional reconstructive procedures to improve aesthetic outcome. 13,16,20 The improvement of oncoplastic techniques may help to curb this high percentage.…”
Section: Introductionmentioning
confidence: 99%
“…26,41,44 Although great strides have been made in breast conserving therapy, the invasive nature of surgical resection oftentimes results in significant scarring and disfigurement, with approximately 20% of patients undergoing breast-conserving therapy unsatisfied with their final breast cosmetic outcome. 13,16 Such cases may undergo additional reconstructive procedures to improve aesthetic outcome. 13,16,20 The improvement of oncoplastic techniques may help to curb this high percentage.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study that aimed to determine what percentage of the cavity reresection specimen contain tumor cells in the case reresection is performed until clear resection margin of at least 5 mm is obtained, we reported that around 30% of specimen re-resected to achieve 5mm free resection margin will contain tumor tissue 16 . From these data, it is clear that resection margin less than 5 mm is definitely not sufficient to achieve tumor negative breast after surgical procedure [17][18] . The other important question is, however, whether obtaining free resection margin will have an impact on local recurrence rate and subsequently on overall survival of breast cancer patients [19][20][21][22][23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 97%
“…As mentioned above, after supportive data from a previous study we decided to evaluate the local relapse free survival in this group of patients in the case the clear resection margin 5 mm is achieved. We always have to keep in mind the importance of cosmetic outcome of breast surgery 18 . We also have to consider the fact that the isolated local relapse does not have to impact the overall survival since the local relapse may be successfully treated by local surgery or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with an expected volume reduction of more than 10%, surgeons should think about the use of oncoplastic surgery [162][163][164] as cosmetic outcome may significantly be impaired. The breast volume reduction of more than 10% reduced the cosmetic result by 50% [163].…”
Section: Indicationmentioning
confidence: 99%